PENINGKATAN KETERAMPILAN BERCERITA MENGGUNAKAN MEDIA BONEKA TANGAN SISWA KELAS III - Putri Shafira Azzahra; Meilan Tri Wuryani; Dian Kusumawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Storytelling is one of the essential language skills that should be developed in elementary school students. However, the storytelling skills of third-grade students were still not optimal, particularly in terms of speaking fluency, intonation, facial expressions, and self-confidence when performing in front of the class. Therefore, hand puppet media were used as a learning tool to help improve students’ storytelling skills. This study aimed to describe the implementation of hand puppet media in storytelling learning activities and to identify the improvement in students’ storytelling skills after the implementation of the media. The study employed a Classroom Action Research (CAR) method conducted in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The subjects of this study were 39 third-grade students at SD Negeri 1 Weleri. Data were collected through observation, storytelling performance tests, interviews, and documentation. The findings showed that the implementation of hand puppet media created a more active, engaging, and enjoyable learning atmosphere, encouraging students to become more confident in telling stories. Improvements were observed in students’ fluency, intonation, facial expressions, and confidence during storytelling activities in front of the class. The students’ average score increased from 64.5 in Cycle I to 77.0 in Cycle II, while the percentage of learning mastery improved from 54% to 85%. Therefore, the implementation of hand puppet media proved effective in improving the storytelling skills of third-grade students at SD Negeri 1 Weleri. ABSTRAK Kemampuan bercerita merupakan salah satu keterampilan berbahasa yang penting dikembangkan pada siswa sekolah dasar. Namun, kemampuan bercerita siswa kelas III masih belum optimal, terutama pada aspek kelancaran berbicara, penggunaan intonasi, ekspresi, dan rasa percaya diri ketika tampil di depan kelas. Oleh karena itu, media boneka tangan digunakan sebagai sarana pembelajaran untuk membantu meningkatkan keterampilan bercerita siswa. Penelitian ini bertujuan untuk mendeskripsikan penerapan media boneka tangan dalam pembelajaran bercerita serta mengetahui peningkatan keterampilan bercerita siswa setelah penerapan media tersebut. Penelitian menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus. Setiap siklus terdiri atas tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah 39 siswa kelas III SD Negeri 1 Weleri. Teknik pengumpulan data melalui observasi, tes keterampilan bercerita, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan media boneka tangan mampu menciptakan suasana pembelajaran yang lebih aktif, menarik, dan menyenangkan sehingga siswa menjadi lebih percaya diri dalam menyampaikan cerita. Peningkatan keterampilan bercerita terlihat pada aspek kelancaran, intonasi, ekspresi, dan keberanian siswa saat tampil di depan kelas. Nilai rata-rata siswa meningkat dari 64,5 pada siklus I menjadi 77,0 pada siklus II, sedangkan persentase ketuntasan belajar meningkat dari 54% pada siklus I menjadi 85% pada siklus II. Dengan demikian, penerapan media boneka tangan terbukti dapat meningkatkan keterampilan bercerita siswa kelas III SD Negeri 1 Weleri.